2018
DOI: 10.1007/s00535-018-1432-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor substrate-4 is overexpressed in colorectal cancer and promotes retinoblastoma–cyclin-dependent kinase activation

Abstract: Taken together, our findings suggest that IRS-4 promotes retinoblastoma-cyclin-dependent kinase activation and it may serve as a pharmacological target since its expression is very low in normal tissue, including colonic epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The tyrosine phosphorylation of IGF-1 receptor has been associated with the resistance of CRC patients to conventional therapies and targeted therapeutic agents [ 26 , 27 ]. This phenomenon may be caused by the increase in IRS-4 levels in CRC tissue [ 23 ]. In the present study, we observed that IRS-4 overexpression in HepG2 and RKO cancer cells is associated with the activation of IGF-1 receptor signalling pathways in the absence of extracellular ligand.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The tyrosine phosphorylation of IGF-1 receptor has been associated with the resistance of CRC patients to conventional therapies and targeted therapeutic agents [ 26 , 27 ]. This phenomenon may be caused by the increase in IRS-4 levels in CRC tissue [ 23 ]. In the present study, we observed that IRS-4 overexpression in HepG2 and RKO cancer cells is associated with the activation of IGF-1 receptor signalling pathways in the absence of extracellular ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of this pathway was associated with the increase in anchorage-independent survival of mammary epithelial cells in culture [ 29 ] and possibly in metastatic dissemination [ 29 ]. Previously, we demonstrated that IRS-4 increased HepG2 [ 10 ] and RKO [ 23 ] proliferation by a Rb-CDK pathway. In addition we showed that overexpression of IRS-4 correlated with clinical staging in colorectal cancer patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations